Exploration of the Application of Gamification Methods in Pancasila Education Learning - Hajar, Nurfahmi; Haris , Hasnawi; Mustari, Mustari; Kasmawati, Andi; Najamuddin, Najamuddin; Sahabuddin , Romansyah (Journal La Edusci, 2025)
This study examines the implementation of gamification in Pancasila Education at the senior high school level within a resource-constrained learning environment. It aims to analyze the design and implementation of gamification, identify challenges encountered during its application, and formulate optimization strategies to enhance student engagement and participation. Using a qualitative descriptive case study approach, data were collected through semi-structured interviews, classroom observations, and document analysis involving one Pancasila Education teacher and eight eleventh-grade students at a public senior high school in West Sinjai Regency. Data were analyzed using an interactive thematic analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that gamification was implemented through structured stages of planning, implementation, and evaluation, incorporating game elements such as points, levels, challenges, badges, and leaderboards via digital platforms including Kahoot, ZepQuiz, Wordwall, and Bamboozle. The application of gamification enhanced student engagement across behavioral, emotional, cognitive, and social dimensions. However, several challenges emerged, including unstable internet connectivity, limited digital devices, uneven student digital literacy, and learner anxiety related to individual competition. To address these issues, teachers adapted instructional designs by employing group-based leaderboards, hybrid online–offline learning activities, and peer-assisted learning strategies. This study demonstrates that gamification can serve as an effective pedagogical approach in Pancasila Education when supported by adaptive instructional design and contextual sensitivity. The originality of this research lies in its evidence that gamification can be meaningfully implemented in value-based subjects within digitally limited school contexts.